Adsorption properties of Pb(II) and Cd(II) in acid mine drainage by oyster shell loaded lignite composite in different morphologies - Wenbo An; Yifan Liu; He Chen; Xueying Sun; Qiqi Wang; Xuechun Hu; Junzhen Di (Scientific Reports, 2024)
Abstract A new idea to alleviate environmental pollution is the development of low-cost adsorbents using natural minerals and fishery wastes to treat high concentrations of heavy metal pollutants in acid mine drainage (AMD). Adsorbent morphology, adsorptive and regenerative capacity, and application potential are limiting factors for their large-scale use. Oyster shells capable of releasing alkalinity were loaded on the surface of lignite to develop two composite adsorbents with different morphologies (powdery and globular) for the treatment of AMD containing Pb(II) and Cd(II). The results show that the ability of the adsorbent to treat AMD is closely related to its morphologies. The pseudo-second-order kinetic model and the Langmuir model are suitable to describe the adsorption process of OS-M(P), and the maximum adsorption saturation capacities of Pb(II) and Cd(II) are 332.6219 mg/g and 318.9854 mg/g, respectively. The pseudo-second-order kinetic model and the Freundlich model are suitable to describe the adsorption process of OS-M(G). A synergistic result of electrostatic adsorption, neutralization precipitation, ion exchange and complex reaction is achieved in the removal of Pb(II) and Cd(II) by two morphologies of adsorbents. The regeneration times (5 times) and recovery rate (75.75%) of OS-M(G) are higher than those of OS-M(P) (3 times) and recovery rate (20%). The ability of OS-M(G) to treat actual AMD wastewater is still better than that of OS-M(P). OS-M(G) can be used as a promising environmentally friendly adsorbent for the long-term remediation of AMD. This study provides a comprehensive picture of resource management and reuse opportunities for natural mineral and fishery wastes.